1988
DOI: 10.3758/bf03197743
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual transfer insimple insight problems

Abstract: Three experiments explored the conditions under which information presented in the first part of an experiment facilitates the subsequent solving of simple insight problems. We argue that previous unsuccessful attempts to obtain such facilitation are attributable to the experimenters' failure to present this information in a form that induces the conceptual operations needed to solve the problem. Substantial facilitation is obtained if the information is presented in a form that induces a few seconds of puzzle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 17 publications
2
52
0
1
Order By: Relevance
“…This distinction made between two kinds of problems has led to consideration that there are two kinds of problem-solving processes: planning and memorising under the constraint of cognitive load for welldefined problems (Anzaı¨& Simon, 1979;Kotovsky & Kushmerick, 1991;Simon, 1979), creativity, insight, and restructuring mental representations of the situation (and particularly the objects it comprises) for ill-defined problems (Duncker, 1945;Kohler, 1964;Lockhart, Lamon, & Gick, 1988;Mayer, 1983;Ohlsson, 1984aOhlsson, , 1984b. Richard, Poitrenaud, and Tijus (1993) have called this distinction into question.…”
mentioning
confidence: 99%
“…This distinction made between two kinds of problems has led to consideration that there are two kinds of problem-solving processes: planning and memorising under the constraint of cognitive load for welldefined problems (Anzaı¨& Simon, 1979;Kotovsky & Kushmerick, 1991;Simon, 1979), creativity, insight, and restructuring mental representations of the situation (and particularly the objects it comprises) for ill-defined problems (Duncker, 1945;Kohler, 1964;Lockhart, Lamon, & Gick, 1988;Mayer, 1983;Ohlsson, 1984aOhlsson, , 1984b. Richard, Poitrenaud, and Tijus (1993) have called this distinction into question.…”
mentioning
confidence: 99%
“…'s (1983) clue statements were transformed into puzzle or problem-oriented forms by Adams et aI. (1988) and Lockhart et al (1988). Compared with the statement forms, these conditions produced superior spontaneous transfer, according to predictions from the framework of transfer-appropriate processing.…”
Section: Problem Solving By Analogymentioning
confidence: 99%
“…Against a tradition that has mainly shown poor transfer of solution methods when hints to use prior analogues have not been provided, a few studies point to the importance of transferappropriate processing (e.g., Adams et al, 1988; Gick & McGarry, 1992;Lockhart, Lamon, & Gick, 1988;Stein, Way, Benningfield, & Hedgecough, 1986). Consider a set of experiments by Needham and Begg (1991): Some of their subjects tried to solve training analogues before they were taught their solutions, while the others studied the analogues and tried to remember them before the solutions were taught.…”
mentioning
confidence: 99%
“…As the emphasis in problemsolving research has shifted to the knowledge required to solve problems, increasing attention has been focused on questions about the access and use of such knowledge (e. g., Adams et al, 1988;Gentner & Landers, 1985;Gick & Holyoak, 1980Holyoak & Koh, 1987;Lockhart, Lamon, & Gick, 1988;Perfetto, Bransford, & Franks, 1983;Ross, 1984Ross, , 1987Ross, , 1989aRoss, , 1989bStein, Way, Benningfield, & Hedgecough, 1986;Weisberg, DeCamillo, & Phillips, 1978). A number of these studies have shown that subjects often fail to transfer relevant knowledge spontaneously to a new situation.…”
mentioning
confidence: 99%
“…Research concerned with the failure to access relevant information has proceeded along two related lines. The first line has tried to identify the factors that might improve access, such as the way in which the relevant information is processed (e.g., Adams et al, 1988;Lockhart et al, 1988), surface similarity (e.g., Gentner & Landers, 1985;Holyoak & Koh, 1987;Ross, 1984Ross, , 1987Stein et al, 1986), context (Spencer & Weisberg, 1986), and the comparison of instances (Dellarosa, 1985;Gick & Holyoak, 1983). The second related line of research has probed the nature of the retrieval process in these problem-solving situations.…”
mentioning
confidence: 99%